2012
DOI: 10.1002/ppul.22747
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopic assessment of airway involvement in children presenting with clinically significant airway obstruction due to tuberculosis

Abstract: Bronchus intermedius and left main bronchus were the commonest sites of airway obstruction. The MTB culture yield from BAL was higher in children with pneumonia when compared to those with airway involvement alone. HIV positive or children with drug resistant TB did not have more severe airway obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…The diagnostic value of mycobacterial culture from BAL is generally accepted to be limited in children with uncomplicated TB with reported culture yields lower or equivalent to gastric aspirate. Higher BAL culture yield (44%) has recently been reported in children with significant airway obstruction, reflecting the higher bacillary load typically associated with severe disease …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The diagnostic value of mycobacterial culture from BAL is generally accepted to be limited in children with uncomplicated TB with reported culture yields lower or equivalent to gastric aspirate. Higher BAL culture yield (44%) has recently been reported in children with significant airway obstruction, reflecting the higher bacillary load typically associated with severe disease …”
Section: Discussionmentioning
confidence: 98%
“…After the procedure, children were transferred back to the pulmonology ward for further observation. Bronchoscopy was systematically performed according to a standard protocol . Observations made under direct bronchoscopic visualization were recorded in a standard data form.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For children with complicated pulmonary diseases, fiberoptic bronchoscopy can assist in diagnosing clinically; also Goussard et al reported that the BALF culture yield was high in children with severe airway obstruction [19], although MTB culture from BALF has limitations to diagnose in children with uncomplicated pulmonary TB because taking BALF is much more invasive [20]. In our setting, all children need to do routine fiberoptic bronchoscopy according to their chest radiograph, and 28.9% of children who suffered from PTB had positive MTB culture, while 8.4% had positive AFB microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In this group of patients, both infection and malnutrition may have had an influence. A previous study on TB associated airway obstruction reported that 50% of children had a weight below the third percentile for age 27 …”
Section: Discussionmentioning
confidence: 98%